Fucosidosis: genetic and biochemical analysis of eight cases. Issue 2 (February 1997) - Cragg, H; Williamson, M; Young, E; O'Brien, J; Alhadeff, J; Fang-Kircher, S; Paschke, E; Winchester, B
Abstract : The molecular basis of the deficiency of alpha-L-fucosidase has been investigated in eight patients who had been diagnosed clinically and enzymatically as suffering from the autosomal recessive lysosomal storage disease fucosidosis. None of the patients had a deletion or gross alteration of the alpha-L-fucosidase gene (FUCA1). Single strand conformation polymorphism (SSCP) analysis followed by direct sequencing of amplified exons and flanking regions identified putative disease causing mutations in six of the patients, who had severe forms of the disease and very low residual alpha-L-fucosidase activity and protein. They were a 10 bp deletion in exon 1 (E113fs), a 1 bp deletion at position -2 of intron 2 (S216fs), a g-->a transition at IVS5+1, point mutations W183X and N329Y in exons 3 and 6, respectively, and a compound allele consisting of a point mutation in the signal peptide in exon 1, P5R, and a 1 bp insertion in exon 6 (Y330fs). One patient in whom an SSCP change was not detected had residual alpha-L-fucosidase activity and cross reacting protein in the heterozygous range and normal metabolism of metabolites containing fucose in his fibroblasts, consistent with the low activity polymorphism. The eighth patient, who had a partial deficiency of alpha-L-fucosidase in her fibroblasts and leucocytes at a young age but normal alpha-L-fucosidase activity and protein at a later age, was homozygous for the common Q281R polymorphism in exon 5. She had no other sequence changes and Kivlin (Peters plus) syndrome has subsequently been diagnosed. The basis of her transient deficiency of alpha-L-fucosidase is not known. The detection of five novel mutations in six severely affected patients confirms the genetic heterogeneity in fucosidosis.